Loss of Pulsatility: Another Cause of Syncope in Patients with Left Ventricular Assist Devices. Issue 10 (November 2020) - Money, Joel E.; Al Danaf, Jad; Nelson, Marisca; Mckellar, Stephen H.; Drakos, Stavros G.; Kemeyou, Line
Abstract : We report a case of a 55-year-old man who presented with recurrent syncope 15 months after HeartWare left ventricular assist device (LVAD) implantation and was found to have diminished LVAD flow and pulsatility on tilt table testing leading to severe orthostatic hypotension (OH). The prevalence of OH is common, but autonomic dysfunction leading to OH has not been well described in patients with chronic LVAD support. The diagnosis of OH in this setting is challenging due to the decreased pulsatility in the flow generated by LVADs, and tilt table testing can be useful in the evaluation of OH in these patients.